Zfp281 orchestrates interconversion of pluripotent states by engaging Ehmt1 and Zic2. (29th November 2019) - Mayer, Daniela; Stadler, Michael B; Rittirsch, Melanie; Hess, Daniel; Lukonin, Ilya; Winzi, Maria; Smith, Austin; Buchholz, Frank; Betschinger, Joerg
Abstract: Developmental cell fate specification is a unidirectional process that can be reverted in response to injury or experimental reprogramming. Whether differentiation and de‐differentiation trajectories intersect mechanistically is unclear. Here, we performed comparative screening in lineage‐related mouse naïve embryonic stem cells (ESCs) and primed epiblast stem cells (EpiSCs), and identified the constitutively expressed zinc finger transcription factor (TF) Zfp281 as a bidirectional regulator of cell state interconversion. We showed that subtle chromatin binding changes in differentiated cells translate into activation of the histone H3 lysine 9 (H3K9) methyltransferase Ehmt1 and stabilization of the zinc finger TF Zic2 at enhancers and promoters. Genetic gain‐of‐function and loss‐of‐function experiments confirmed a critical role of Ehmt1 and Zic2 downstream of Zfp281 both in driving exit from the ESC state and in restricting reprogramming of EpiSCs. Our study reveals that cell type‐invariant chromatin association of Zfp281 provides an interaction platform for remodeling the cis‐regulatory network underlying cellular plasticity. Synopsis: If reprogramming of somatic cells requires the reversal of developmental mechanisms is unclear. In this study, comparative large‐scale screening identifies zinc finger transcription factor Zfp281 as a bi‐directional cell state transition regulator of mouse naïve pluripotency. Zfp281 controls interconversion of naïve embryonic stem cells and primed epiblast stem cells. Zfp281 occupies cis‐regulatory DNA elements (CREs) independent of the cell state. H3K9 methyltransferase EHMT1 and transcription factor Zic2 interact with Zfp281 preferentially in differentiated cells. Genetic depletion of Ehmt1 and Zic2 recapitulates cell state transition phenotypes caused by absence of ZFP281. Zfp281 activates Ehmt1 and recruits Zic2 to CREs. Abstract : Cell type‐invariant chromatin association of zinc finger transcription factor Zfp281 facilitates bidirectional regulation of mouse naïve pluripotency.